Katsomukset ja kulttuuriset työkalut modernin elämän palapelissä - Utriainen, Terhi (Annales Academiae Scientiarum Fennicae, 2023)
Religion and other views of life are often studied by applying the notions of identity and worldview. My article offers to supplement these perspectives by that of cultural tools. Pluralistic societies afford multiple cultural tools with which individuals and groups can try to adjust their position and enhance their possibilities of action in the midst of the often precarious and rapidly changing situations of modern life. Both scientific and religious, or “spiritual”, tools are available, and they may be flexibly applied and, also, combined in different ways. I reflect on the question of cultural tools drawing from the recent research conducted by my colleagues as well as by myself on the following three subject areas: Esoteric beliefs and practices in the shadow of mainstream religion, transforming rituals of death, and the interest in learning from new kinds of religion and spirituality.